Citizen engagement in social health insurance purchasing, in selected counties in Kenya - Mwangi, Eunice M.; Tenambergen, Wanja M.; Mapesa, Job O.; Mutai, Isaac K. (International Journal Of Community Medicine And Public Health, 2019)
Background: National hospital insurance fund (NHIF) uses capitation as a strategic purchasing model to provide primary care health services (PCHS). This study sought information on citizen knowledge of PCHS benefit package, NHIF communication to citizens, determination of citizen views and values, NHIF accountability to citizens, citizen choice of PCHS provider and how these factors influence citizen access to NHIF, PCHS. Methods: This was a cross sectional research conducted between March 2017 to March 2018. 426 patients were sampled from Nyandarua and Nakuru Counties. Results: 366 (93%) patients knew the PCHS benefit package, 226 (57%) said NHIF communication to them was adequate, 280 (71%) said NHIF does not take into account their view and values, 272 (69%) said NHIF is not accountable to them, 269 (68%) knew how to select an outpatient facility, 111 (28%) said they did not receive NHIF, PCHS. Multivariate logistics regression analysis of citizen engagement factors and access to PCHS, indicate that NHIF communication to citizens (p<0.05, OR=2.358, 95% CI [1.399-3.975]), purchaser accountability (p<0.05, OR=2.073, 95% CI [1.017-4.226]) and provider choice (p<0.05, OR=2.990, 95% CI [1.817-4.920]) added significantly to the regression model. Conclusions: There is inadequate engagement of citizens in NHIF decision making which may hinder access to NHIF PCHS, therefore NHIF should establish citizens’ needs and preference through public forums, elicit citizens’ feedback, act on complains when raised, inform citizens on how the capitation system works and NHIF should visit health facilities regularly to establish if patients are accessing PCHS.